A study on the food fraud of national food safety and sample inspection of China. (October 2020) - Li, Dan; Zang, Mingwu; Li, Xiaoman; Zhang, Kaihua; Zhang, Zheqi; Wang, Shouwei
Abstract: National food safety and sample inspection is important for the discovery of food safety problems in China. Due to increases in sample quantity since 2014, many food fraud (FF) problems, such as lean meat essence and malachite green added, have been identified through sample inspections. To gain insights into the current situation of FF, we studied failed samples involved FF identified through sample inspection from 2014 to July 2018. The regional distribution, food categories, food sampling sites, FF types and adulterated substances of these samples were analyzed. Unlike many studies, the definition of FF in this study focused on the intrinsic state of the food rather than the subjective intent of the behavior. Unintentional FF might occur due to lack of knowledge, facilities or resources. The results showed the following: 1) of the 26, 708 batches of failed samples, 17.98% involved FF; 2) the failed samples that involved FF were sampled and produced in more than 30 provinces, and Hubei, Shandong and Sichuan were the top three providences; 3) the failed samples involving FF were mainly found in circulation links, which accounted for 63.99% of the failed samples; and 4) processed foods exhibited the highest rate of failed samples involving FF. The subcategories of food involving FF mainly included (i) alcohol, (ii) aquatic products, (iii) eggs, (iv) processed aquatic products, and (v) pastries, which accounted for 17.91%, 13.47%, 5.46%, 5.19%, and 5.12% of failed samples involving FF, respectively. 5) In addition, artificial enhancement was identified as the major FF type, accounting for 99.79% of failed samples involving FF. 6) Food additives and banned veterinary drugs were the major adulterated substances, accounting for 87.79% of all adulterations in failed samples involving FF. The results of this study might not be completely consistent with the actual situation of FF because sample inspection is limited by the current test items and sampling range. The results of this study are helpful for understanding the current situation and characteristics of FF, updating the FF database, and providing a reference for the prevention and control of FF in China. Highlights: Sample inspection is important for identifying food fraud problems in China. 17.98% of 26, 708 batches of failed samples identified from 2014 to July 2018 involve food fraud. Food additives and banned veterinary drugs accounting for 87.79% of all adulterations.